Expression of the Arabidopsis vacuolar H+‐pyrophosphatase gene (AVP1) improves the shoot biomass of transgenic barley and increases grain yield in a saline field. Issue 3 (22nd November 2013) - Schilling, Rhiannon K.; Marschner, Petra; Shavrukov, Yuri; Berger, Bettina; Tester, Mark; Roy, Stuart J.; Plett, Darren C.
Summary Cereal varieties with improved salinity tolerance are needed to achieve profitable grain yields in saline soils. The expression of AVP1, an Arabidopsis gene encoding a vacuolar proton pumping pyrophosphatase (H+‐PPase), has been shown to improve the salinity tolerance of transgenic plants in greenhouse conditions. However, the potential for this gene to improve the grain yield of cereal crops in a saline field has yet to be evaluated. Recent advances in high‐throughput nondestructive phenotyping technologies also offer an opportunity to quantitatively evaluate the growth of transgenic plants under abiotic stress through time. In this study, the growth of transgenic barley expressing AVP1 was evaluated under saline conditions in a pot experiment using nondestructive plant imaging and in a saline field trial. Greenhouse‐grown transgenic barley expressing AVP1 produced a larger shoot biomass compared to null segregants, as determined by an increase in projected shoot area, when grown in soil with 150 mm NaCl. This increase in shoot biomass of transgenic AVP1 barley occurred from an early growth stage and also in nonsaline conditions. In a saline field, the transgenic barley expressing AVP1 also showed an increase in shoot biomass and, importantly, produced a greater grain yield per plant compared to wild‐type plants. Interestingly, the expression of AVP1 did not alter barley leaf sodium concentrations in either greenhouse‐ or field‐grown plants. This study validates our greenhouse‐based experiments and indicates that transgenic barley expressing AVP1 is a promising option for increasing cereal crop productivity in saline fields.